Confucianism, Business Leaders, and Party-State Power in Contemporary China - Lan Jiang Fu (Journal of Current Chinese Affairs)
From the beginning of the twenty-first century onwards, China has witnessed a Confucian revival in the business world. Often associated with a revitalisation of cultural tradition among the population, this new trend is characterised by a resurgence of the Confucian merchant (儒商, rushang ) model, an ancient term that originally referred to a new type of merchants in the Ming Dynasty (1368–1644), who were close to literati circles. In parallel with this increasing interest in Confucianism by many economic elites, there has been an integration of certain elements of Confucianism into official political discourse through various moral edification campaigns. Based on an analysis of this new official discourse and the fieldwork we carried out between 2016 and 2020 within three private companies, this article aims to analyse interactions between three elements: Confucianism, party-state power, and business leaders claiming to be “Confucian.”